PARTISIPASI POLITIK SUKU BATAK TOBA DALAM PEMILIHAN BUPATI DAN WAKIL BUPATI OGAN KOMERING ULU PADA PILKADA SERENTAK 2015 - Aprildo, Albert; Suka Arjawa, I Gusti Putu Bagus; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT Political participation is an important part of democracy. As part of the Ogan Komering Ulu citizens, the Toba Batak tribe is expected to make political participation in the election of the regent and deputy of Ogan Komering Ulu district. The results of this study found the political participation conducted by the Toba Batak tribe in the Ogan Komering Ulu regent and deputy district head election was political participation in voting and a small part of the Toba Batak tribe became a successful team. The results of this study the reasons for Toba Batak tribe to conduct political participation in the election of the regent and deputy head of Ogan Komering Ulu in 2015 were the first, the reason for rational assessment. Second, the reason for political awareness. Third, the reason for the issue of the local son. Key Words: Political Participation, Toba Batak Tribe, Simultaneous Local Election